Online Shopping Experience in Minimarket and The Impact on Sales Figure - Christopher Winson Budiman; Alfa Ryano Yohannis (Politeknik Pertanian Negeri Samarinda, 2025)
The rise of digital technology has transformed consumer shopping behavior, with online shopping emerging as a dominant force in retail. This study investigates the online shopping experience in minimarkets, a segment traditionally reliant on in-person transactions and explores its impact on sales figures. As consumer preferences increasingly shift towards convenience and accessibility, minimarkets must adapt to integrate online platforms that cater to these demands. This research employs a mixed-methods approach, combining quantitative analysis of sales data from selected minimarkets with qualitative insights gathered through customer surveys and interviews. Key findings reveal that the online shopping experience significantly influences customer satisfaction and purchasing behavior in minimarkets. Factors such as website usability, product variety, delivery options, and customer service quality are found to be critical determinants of the online shopping experience. Additionally, the study highlights that effective online engagement strategies such as personalized promotions, user-friendly interfaces, and responsive customer support can lead to increased customer loyalty, higher average order values, and improved overall sales performance. The research further demonstrates that the integration of online shopping platforms not only complements traditional brick-and-mortar operations but also attracts new customer segments who prioritize convenience and accessibility. In particular, the ability to shop online allows minimarkets to capitalize on trends such as click-and-collect services and home delivery, which have gained traction during the COVID-19 pandemic and continue to shape consumer expectations. Furthermore, the analysis reveals a direct correlation between enhanced online shopping experiences and improved sales figures, suggesting that minimarkets that invest in their digital presence can achieve significant competitive advantages in a rapidly evolving retail landscape. This paper contributes to the growing body of literature on online retailing by providing empirical evidence on the effectiveness of online shopping experiences in small-format retail environments. It offers actionable insights for minimarket managers and stakeholders looking to optimize their online platforms, enhance customer engagement, and ultimately drive sales growth. The findings emphasize the necessity for minimarkets to embrace digital transformation as an integral component of their business strategy to remain relevant and competitive in today’s consumer-driven market